Metode Modified-Partial Capacity Design (M-PCD) Dengan Kolom Elastis 30%: Studi Kasus Bangunan Beton Bertulang Persegi 6 Lantai - Pamuda Pudjisuryadi; Benjamin Lumantarna; Valerie Christabel Hendrarto; Jessica Amabel Salim (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
One alternative for designing earthquake-resistant structures is the Partial Capacity Design (PCD) method. Unlike the traditional capacity design method, which enforces a strong column weak beam to control side sway mechanism, PCD allows for a partial side sway mechanism. In this approach, all beams and some columns are permitted to experience plastic bending (KP), while the remaining columns are designed to stay elastic (KE). Over time, the PCD method evolved into the modified-PCD (M-PCD), which incorporates both linear and non-linear phases in structural analysis. This study examined a 6-story building with a square plan,where 30% of the columns remained elastic. The building's performance was evaluated through non-linear time history analysis using modified ground acceleration in line with the design spectrum response. Results indicated that the 6-story structure performed well overall, meeting regulatory requirements for collapse mechanism and drift. However, plastic hinge damage exceeded FEMA 273 standards.